Incentive Factors for Social Entrepreneurship Adoption - Lucia Durac; Liliana Mihaela Moga (Communications of International Proceedings, 2020)
The stakeholders’ reaction caused by the posibility to use a new service, product or conduct a traditional activity in a new way is a continuous subject of study for the researchers. An important role is played by the study of incetinve factors that influence the decision to adopt an innovative activity like the social entrepreneurship is. The approaching of the the social mission by the entrepreneurs leads to the identification of solutions to problems and the improvement of the living conditions of the community, bringing social innovation. The paper aims to identify the factors that influence the adoption of the ​​social entrepreneurship using the diffusion of innovation theory. The research intends to complete the existing entrepreneurial research by identifying the role of the individual entrepreneur in bringing social innovation or the emphasis on the importance of traditional entrepreneurship. The study contributes to determining the factors that influence the orientation of entrepreneurs towards social entrepreneurship approached like an innovative entrepreneurship.